2020
DOI: 10.1101/2020.08.17.254078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating genetics, morphology, and fungal host specificity in conservation studies of a vulnerable, selfing, mycoheterotrophic orchid

Abstract: Mycoheterotrophic plants derive most or all carbon and nutrients from fungal partners and represent poorly understood components of forest biodiversity. Many are rare or endangered yet can be ecological indicators of forest ecosystem function due to their often highly specific fungal host requirements. One such species is the IUCN red-listed (vulnerable), fully mycoheterotrophic orchid, Corallorhiza bentleyi. This recently described species is among the rarest plants in Appalachia, known from five counties in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Additional evidence of the recovery of population genomic signal in these data was our identification of fixed homozygous sites exclusive to cleistogamous individuals. We find the general congruence of visually scored ISSR banding patterns in Fama et al (2021) with the more sensitive, sequence-based nature of ISSRseq to be additional corroboration of our new method.…”
Section: Bentleyisupporting
confidence: 63%
See 2 more Smart Citations
“…Additional evidence of the recovery of population genomic signal in these data was our identification of fixed homozygous sites exclusive to cleistogamous individuals. We find the general congruence of visually scored ISSR banding patterns in Fama et al (2021) with the more sensitive, sequence-based nature of ISSRseq to be additional corroboration of our new method.…”
Section: Bentleyisupporting
confidence: 63%
“…ISSRseq corroborated results of a traditional ISSR investigation study of C. bentleyi conducted previously by our group. Fama et al (2021) scored ISSR bands visually for two primers used in this study and found that 89% of molecular variance occurred within populations.…”
Section: Bentleyimentioning
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, in mycoheterotrohic orchids, cryptic specialisation for fungi may arise despite high gene flow if plants' fungal preferences are selected in a local environment throughout the species range, as expected in the geographic, mosaic model of coevolution (Thompson 2005). Unfortunately, population genetic studies that could help to elucidate the extent of genetic variation as well as patterns of gene flow for mycoheterotrophic plants (orchids in particular) are still rare (but see Alves et al 2021;Beatty and Provan 2011a, b;Fama et al 2021;Hopkins and Taylor 2011;Klooster and Culley 2010).…”
Section: Introductionmentioning
confidence: 99%